Computational studies of talin-mediated integrin activation - Kalli, A (2013)
Integrins are large heterodimeric (αβ) cell surface receptors that play a key role in the formation of focal adhesion complexes and are involved in various signal transduction pathways. They are ‘activated’ to a high affinity state by the formation of an intracellular complex between the membrane, the integrin β-subunit tail and talin, a process known as ‘inside-out activation’. The head domain of talin, a FERM domain homologue, plays a vital role in the formation of this complex. Recent studies also suggest that kindlins act in synergy with talin to induce integrin activation. Despite much available structural and functional data, details of how talin activates integrins remain elusive. In this thesis a multiscale simulation approach (using a combination of coarse-grained and atomistic molecular dynamics simulations) together with NMR experiments were employed to study talin-mediated integrin inside-out activation. A number of novel insights emerged from these studies including: (i) the crucial role of negatively charged lipids in talin/membrane association; (ii) a novel V-shape conformation of the talin head domain which optimizes its interactions with negatively charged lipids; (iii) that interactions of talin with negatively charged moieties in the membrane orient talin to optimize interactions with the β cytoplasmic tail; (iv) that binding of talin to the β cytoplasmic tail promotes rearrangement of the integrin TM helices and weakens the integrin α/β association; and (v) that an increase in the tilt angle of the β integrin TM helix initiates a scissoring movement of the two integrin TM helices. These results, combined with experimental data, provide new insights into the mechanism of integrin inside-out activation. The same multiscale approach was used to demonstrate the crucial role of the Gx3G motif in the packing of the integrin transmembrane helices. Using recent structural data the integrin/talin complex was modelled and inserted in bilayers which resemble the biological plasma membrane. The results demonstrate the dynamic nature of the integrin receptor and suggest that the integrin/talin complex alters the lipid organization and motion in the outer and inner bilayer leaflets in an asymmetric way and that diffusion of lipids in the vicinity of the protein is slowed down. The work in this thesis demonstrates that multiscale simulations have considerable strengths when applied to investigations of structure/function relationships in membrane proteins.